A multi-stage remanufacturing approach for life extension of safety critical systems - Animah, Isaac; Shafiee, Mahmood; Simms, Nigel J.; Tiwari, Ashutosh (Elsevier, 2017)
Life extension of safety critical systems is gaining popularity in many industries due to the increasing demand in world's energy consumption and the strong desire to reduce carbon emissions by different countries. Identification and implementation of a suitable life extension strategy enables safety critical systems to perform their intended functions under stated condition for an extended period of time beyond original design life. In the past, the viability analysis of life extension strategies has been undertaken based on the accumulated knowledge and experience of Original Equipment Manufacturer (OEM), maintenance engineers and inspectors. These approaches involving expert judgement are qualitative in nature and based on conservative assumptions, which may lead to inaccurate conclusion or misleading recommendations to asset managers. Therefore, it is crucial to develop an approach consisting of methods to determine the technical condition of components, estimate the cost of life extension interventions and to analyze carbon footprints. “Remanufacturing” is considered as a suitable end-of-life strategy that can help reduce the overall environmental burden from the product by processing waste materials while at the same time keeping reliability high. Due to the advantages of remanufacturing, it is widely applied for life extension purposes in safety critical industries such as offshore oil and gas, nuclear power, petrochemical, renewable energy, rail transport, aviation, shipping, and electricity distribution and transmission. In this paper, a multi-stage approach is presented to analyze the impact of remanufacturing of safety critical systems on the performance of industrial operations in terms of total cost and carbon footprint. In this approach, the equipment health status is determined by modelling the degradation of the system and then the maintenance costs and carbon footprint are calculated. For the purpose of clarity, the proposed model is applied to an air compressor system and the results are discussed.
Keywords: Life extension; Remanufacturing; Safety critical asset; Reliability; Maintenance; Greenhouse gases emission